Assessing the causal role of hypertension on left atrial and left ventricular structure and function: A two-sample Mendelian randomization study - Sun, Yancui; Zhang, Ying; Xu, Nan; Bi, Cheng; Liu, Xiaojie; Song, Wei; Jiang, Yinong (Frontiers in Cardiovascular Medicine, 2022)
Aim The aim of this study was to investigate whether hypertension may be causally linked to left atrial (LA) and left ventricular (LV) structure and function. Methods and results We performed a two-Mendelian randomization (MR) analysis implementing the results from the FinnGen large-scale, genome-wide association study for hypertension (N = 218,754), and LV (N = 16,923) and LA studies (N = 35,648) by the UK Biobank to identify genetic instruments. The MR analysis was implemented using an inverse-variance weighted (IVW) approach. We identified a positive potential causal relationship between hypertension and indices for the LA maximum (LAmax with causal estimates of 0.126 [95% CI, (0.093 to 0.160)]); LA minimum (LAmin with causal estimates of 0.122 [95% CI, (0.089 to 0.156)]); LV function (causal estimates are LV end-diastolic volume (LVEDV), 0.078 [95% CI, (0.003 to 0.153)]; LV end-systolic volume (LVESV), 0.102 [95% CI, (0.030 to 0.173)]; LV mass (LVM), 0.171 [95% CI, (0.108 to 0.233)]; and LV mass to end-diastolic volume ratio (LVMVR at 0.098 [95% CI, (0.048 to 0.149)], respectively), which was directionally concordant with other robust MR methods. Other than this, we observed a significantly negative causal relationship between hypertension and the LA active emptying fraction (LAAEF), the LA passive emptying fraction (LAPEF), and the LA total emptying fraction (LATEF). Conclusion Our genetic analyses demonstrated a potential causal relationship between hypertension and the left atrium and left ventricle’s structures and functions.